Ateliê de costura: experiências e processos na educação não formal - Pupatto, Marcela Gomes (2022)
The research Ateliê de Costura (Sewing Workshop): experiences and processes in non-formal education had as a general objective; to Analyze the educational processes developed in the Ateliê de Costura project, at the Program of Technologies and Arts in Sesc Pinheiros. As a specific objective it will identify, based on face-to-face practices, online and remote learning (carried out between 2019 and 2020) how these experiences were developed in this context of non-formal education. The relationship established between two concepts, Sewing Techniques, as the technological tool of sewing and to Sew, as an educational, symbolic and metaphorical action to get together with someone, was understood in the construction of significant educational experiences for the people involved in the project. The theoretical basis of the research is composed of the contributions of Trilla and Ghanem (2008) and Gohn (2015) (nonformal education), Freire (1967, 1996) (liberating education and pedagogy of autonomy), Noffs and Santana (2016) (didactic transposition), Tardif (2014) (teaching knowledge), Bondía (2002) (reflections on the experience), Hernández-Hernández and Sancho-Gil (2019) (rhizomatic curriculum), among others. The methodological approach chosen was qualitative research through documental, bibliographic and narrative analysis. Different educational perspectives have been observed in face-to-face and remote teaching and an inseparability between Sewing Techniques and to Sew, between technology and human relationships. These studies showed that the Ateliê de Costura, as an instrument of cultural manifestation and artistic creation, promotes the development of teaching professionalism through the use of new materials and technological tools in order to face the challenges in the exercise of humanized teaching through making bonds, in the face-to-face, online and remote modalities, with a diverse and unknown audience, and identifies the didactic transposition as a pedagogical alternative for the adaptation of knowledge in a new context. The Ateliê de Costura, its experiences and processes, reaffirm the relevance of non-formal education in the personal and technological formation of the person, as its educational proposals make it possible to learn how to handle technical tools such as needles, the sewing machine, knowledge of different types of fabric and as well as promoting the learner's autonomy, favoring interpersonal relationships, strengthening the person as being made feel responsible for their learning process, thus reaffirming everyone's right to education